2011
DOI: 10.3892/mmr.2011.617
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative effects of Chinese herb Cornus officinalis in a cell culture model for estrogen receptor‑positive clinical breast cancer

Abstract: anti-prolifertive E 2 metabolite 2-hydoxyestrone (2-OHE 1 ), a 63.6% decrease in the formation of the pro-mitogenic metabolite 16α-hydroxestrone (16-αOHE 1 ) and a 9.1% decrease in the formation of mitogenically inert metabolite estrone (E 3 ). These alterations led to a 14.5-fold increase in the 2-OHE 1 :16α-OHE 1 , and a 3.3-fold increase in the E 3 :16α-OHE 1 ratios. These data validate a rapid cell culture-based mechanistic approach to prioritize efficacious herbal medicinal products for long-term animal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 33 publications
1
55
0
1
Order By: Relevance
“…In addition, the E 3 : 16α-OHE 1 ratio was increased by about 25 fold in response to treatment with LBF and LBB. These data suggest that EG and CO function predominantly via favoring the formation of anti-proliferative 2-OHE 1 [14,23]. On the other hand, LBB and LBF function via increased formation of 2-OHE 1 as well as via accelerated conversion of the promitogenic16α-OHE 1 to relatively inert E 3 [15].…”
Section: Modulation Of End Point Biomarkers By Herbal Extractsmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition, the E 3 : 16α-OHE 1 ratio was increased by about 25 fold in response to treatment with LBF and LBB. These data suggest that EG and CO function predominantly via favoring the formation of anti-proliferative 2-OHE 1 [14,23]. On the other hand, LBB and LBF function via increased formation of 2-OHE 1 as well as via accelerated conversion of the promitogenic16α-OHE 1 to relatively inert E 3 [15].…”
Section: Modulation Of End Point Biomarkers By Herbal Extractsmentioning
confidence: 79%
“…The observed reduction in the number of AI colonies in response to treatment with herbal extracts provides evidence for the efficacy of these extracts towards reduction of breast cancer risk [14,15,23].…”
Section: Model: Mcf-7mentioning
confidence: 93%
See 1 more Smart Citation
“…These agents, due to their inherently minimal toxicity, may provide testable alternatives for limitations of conventional chemo-endocrine and small molecular-targeted therapeutic options. Previously published data on cell culture models for Luminal A, HER-2 enriched and triple negative molecular subtypes of clinical breast cancer have demonstrated that several mechanistically distinct natural phytochemicals and herbal extracts function as cytostatic and pro-apoptotic agents conferring potent growth inhibitory efficacy in these clinically relevant model systems (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Growth Inhibitory Efficacy Of Natural Products In a Model Fomentioning
confidence: 99%
“…Anchorage-independent growth is a sensitive and specific in vitro surrogate endpoint for the tumorigenic potential of carcinoma-derived cell lines (12)(13)(14)(15)(19)(20)(21). For this assay, 184-B5 and MDA-MB-231 cell lines at a predetermined cell density were suspended in 0.33% agar and overlaid on a basement layer of 0.6% agar.…”
Section: Mechanistic Biomarkersmentioning
confidence: 99%